Implementación Active Directory aplicando el estándar 802.1x, dentro de la red LAN y WLAN de la Universidad Nacional de Loja. - Ocampo Vélez, Lenin Sebastián (2016)
This draft is based on qualifications deploying Active Directory using standard 802.1X security on the LAN and WLAN at the National University of Loja. In order to obtain an authentication mechanism for each of the people who use the data network of the institution, thus avoiding various network problems, problems such as addresses IP's losses, attacks on servers of the institution among the main ones. For the correct development of the aforementioned project it was necessary to use a methodology which consists of four stages each with several points or items to deliver. As to procedures for project development, various techniques were necessary, such as interviews, a major he's performed the person in charge of network management at the university, also interviews necessary knowledge of various subjects was conducted in few handling, design and network management. Direct observation and personal conversations with various officials of the institution was also performed. To install the tool, Active Directory, it was necessary to lift the Windows Server 2012 operating system, the same that has acquired licensing by the Telecommunications and Information Unit, configuring network equipment, equipment was needed as well AP's Switch's which are the main provider on the institution. To use the security standard was necessary to create a RADIUS server client. Successfully completing our graduation project.